Pattern of Developmental Dental Anomalies in Patients Visiting Sardar Begum Dental College, Peshawar (Medical Forum Monthly, 2020)
Objective: To determine the pattern of developmental dental anomalies, compare age and to identify the most common anomaly.Study Design: Descriptive study.Place and Duration of Study: This study was conducted at the Sardar Begum Dental College, Ghandhara University, Peshawar during six months period in the year 2016.Materials and Methods: This study was carried out on 350 patients with developmental dental anomalies. Preoperative data were collected through history and clinical examination. Each patient was evaluated for dental anomalies to identify the pattern, most common anomaly and compare the age distribution of anomalies. Statistical analysis included descriptive statistics and χ2 test. Results were considered significant if P<0.05.Results: The age range was 8-20 years and maximum number of patients presented in 17-20 years age group (46%). The commonest anomaly was rotation (28%) followed by cusp of Carabelli (14.3%). Rotation was most common in 17-20 years age group. Cusp of Carabelli was most common in 13-16 group and in 8-12 years age group microdontia.Conclusion: Early detection of anomalies is important to prevent complications.